Complete versus culprit only revascularization in ST-elevation myocardial infarction—a perspective on recent trials and recommendations - Andries, Gabriela; Khera, Sahil; Timmermans, Robert J.; Aronow, Wilbert S. (Journal of Thoracic Disease, 2017)
The presence of multivessel coronary artery disease (CAD) is strongly associated with higher 30-day mortality, reduced myocardial reperfusion success, reinfarction, and occurrence of major adverse cardiac events (MACE) at 1 year compared with single-vessel CAD. Despite higher morbidity and mortality in patients with ST-elevation myocardial infarction (STEMI) and coexistent multivessel CAD, major guidelines recommended against percutaneous coronary intervention (PCI) on non-culprit lesions at the time of primary PCI in patients with STEMI who are hemodynamically stable. The presence of multivessel CAD often poses a therapeutic dilemma for interventional cardiologists. A few larger scale randomized controlled trials (RCTs) and meta-analyses have been conducted. The conclusions regarding multivessel PCI generally trend towards lower risk of MACE, repeat revascularization, with similar risks of recurrent myocardial infarction (MI) and mortality. However, none of the RCTs were adequately powered for hard outcomes of death and MI.